Full hydrodynamic reversibility of the weak dimerization of vancomycin and elucidation of its interaction with VanS monomers at clinical concentration. Issue 1 (December 2017) - Phillips-Jones, Mary; Lithgo, Ryan; Dinu, Vlad; Gillis, Richard; Harding, John; Adams, Gary; Harding, Stephen
Abstract The reversibility and strength of the previously established dimerization of the important glycopeptide antibiotic vancomycin in four different aqueous solvents (including a medically-used formulation) have been studied using short-column sedimentation equilibrium in the analytical ultracentrifuge and model-independent SEDFIT-MSTAR analysis across a range of loading concentrations. The change in the weight average molar massM w with loading concentration was consistent with a monomer-dimer equilibrium. Overlap of data sets of point weight average molar massesM w (r ) versus local concentrationc (r ) for different loading concentrations demonstrated a completely reversible equilibrium process. At the clinical infusion concentration of 5 mg.mL−1 all glycopeptide is dimerized whilst at 19 µg.mL−1 (a clinical target trough serum concentration), vancomycin was mainly monomeric (<20% dimerized). Analysis of the variation ofM w with loading concentration revealed dissociation constants in the range 25-75 μM, commensurate with a relatively weak association. The effect of two-fold vancomycin (19 µg.mL−1 ) appears to have no effect on the monomeric enterococcal VanS kinase involved in glycopeptide resistance regulation. Therefore, the 30% increase in sedimentation coefficient of VanS on adding vancomycin observed previously is more likely to be due to a ligand-induced conformational change of VanS to a more compact form rather than a ligand-induced dimerization.